Efforts of Teachers and Parents in Developing Children's Morals Through Integrated Communication Methods in Early Childhood - Nur Thila Syarofa; Ferdian Utama; Yuning Eka Rahma Wati (Bulletin of Early Childhood, 2026)
This research is motivated by the continued discovery of early childhood behavior that does not reflect commendable morals, such as the habit of speaking rudely and swearing, which indicates a lack of synchronicity between habits at school and parenting patterns at home. This study aims to describe the collaborative and participatory efforts of teachers and parents in developing children's morals through integrated communication methods at RA Nurul Huda Bandar Mataram. This field research with a descriptive qualitative approach involved the principal, class teachers, parents/guardians of students, and students. Data collection through observation, in-depth interviews, and documentation. Data analysis used the inductive model of Miles, Huberman, and Saldaña. Data validity was tested by credibility, transferability, dependability, and confirmability. The results of the study indicate that efforts to develop children's morals are carried out effectively through integrated communication methods with collaborative dimensions (joint design of behavioral targets) and participatory (active involvement of parents as subjects). Teachers and parents optimize contact books, private WhatsApp messages, direct dialogue, and parenting programs, implementing role-modeling and habit-building strategies in a coordinated manner. This collaboration has been proven to reduce children's habit of using bad language and prevent confusion about values, as rules of good manners are consistently reinforced at school and at home.